FRI0309 Type I Interferon Activity Is Associated with Mucocutaneous but Not Musculoskeletal Disease Activity in Systemic Lupus Erythematosus. (15th July 2016) - Mohamed, A.A.A.; El-Sherbiny, Y.; Hensor, E.M.; Md Yusof, M.Y.; Goma, S.H.; Abda, E.A.; Abd-Allah, F.M.; Emery, P.; Vital, E.
Abstract : Background: SLE is clinically and immunologically heterogeneous. Type I interferons (IFN-I) are pathogenic but expression of IFN-I stimulated genes varies. Many existing reports on clinical phenotype and IFN-I were limited by using categorical measures of IFN-I and disease activity scores that were not organ-specific. IFN-I targeted therapies are in development. Objectives: To define the clinical phenotype of IFN-I mediated SLE. Methods: 108 SLE patients and 20 age and sex matched healthy controls were studied. Activity was measured using BILAG-2004. PBMCs were collected for gene expression analysis using TaqMan. Relative expression of 7 interferon stimulated genes was In-transformed, normalized to healthy control and summed to derive a 7-gene IFN-I score. Results: The most common activity was mucocutaneous and musculoskeletal, which were analysed in detail (Table 1 ). The relationship between activity and IFN-I score differed between these domains. Overall, IFN-I scores were higher in active mucocutaneous disease. Scores were more variable for BILAG B: this was explained by subtype of BILAG B disease. IFN-I score was increased in subacute and discoid forms (25.3 (16.8–32.9), n=7) compared to acute forms (18.4 (4.9–31), n=15). Score was also higher in patients with anti-Ro60. In contrast, there was no relationship between musculoskeletal disease activity and IFN-I score. Numbers of patients with renal, haematological and neuropsychiatric activity were limited but there was a trend to higher IFN-I scores with disease activity. Conclusions: We identify a relationship between clinical presentation of SLE and IFN-I. High IFN-I activity is linked to anti-Ro60 and non-acute forms of skin disease. We previously reported a worse response to rituximab in this subgroup, whilst response in musculoskeletal disease was consistently good. Measurement of B cell and interferon biomarkers may therefore be important in the selection of the most appropriate targeted therapy for SLE. Disclosure of Interest: None declared